Studi Kasus : Penerapan Evidence Based Nursing Foot Massage terhadap Penurunan Nyeri Akut pada Pasien Post Sectio Caesarea - Ika Nur Azizah; Endah Sari Purbaningsih; Erida Fadila (Antigen : Jurnal Kesehatan Masyarakat dan Ilmu Gizi, 2026)
Background: Pain is a common problem among post-cesarean section patients due to surgical tissue trauma, which can hinder mobilization and recovery. Foot massage is one of the nonpharmacological interventions that can help reduce pain. Objective: To determine the application of Evidence-Based Nursing through foot massage therapy for acute pain in post-cesarean section patients. Methods: A case study involving five post-cesarean section patients, with pain measured using the Numeric Rating Scale (NRS) before and after a foot massage intervention lasting approximately 15 minutes. Results: All patients experienced a reduction in pain from a range of 5–7 to 2–4 following the intervention. Patients also appeared more relaxed and comfortable. Implications: Foot massage is effective in reducing acute pain in post-cesarean section patients and can be used as a nonpharmacological intervention in nursing care. This intervention also has the potential to enhance patient comfort, support the recovery process, accelerate early mobilization, and serve as a safe complementary therapy that is easy for nurses to implement.